2021
DOI: 10.1002/celc.202100795
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of N,P‐codoped Hard Carbon Nanoporous Microspheres from Lignin for High‐Performance Anodes of Sodium‐Ion Batteries

Abstract: We demonstrate a facile emulsion‐solvent evaporation process to easily convert lignin into nanoporous N,P‐codoped hard carbon microspheres. The combined physiochemical characterizations indicate this material possesses micro‐structure suitable for electrochemical energy storage. The electrochemical measurements of sodium ion battery (SIB) show that such lignin‐derived carbon microspheres also follow the widely‐accepted adsorption‐intercalation Na‐storage mechanism. The Na+ diffusion coefficient in as‐obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In addition, heteroatom doping and loading of sodium storage particles on lignin‐derived hard carbon could also effectively improve the sodium storage performance. Zhang et al [ 112 ] used lignin as a carbon source to synthesize N, P co‐doped hard carbon microspheres with controlled microstructure and morphology by an emulsion‐solvent evaporation method mediated by (NH 4 ) 2 HPO 4 (Figure 13a). The results showed that N, P‐heteroatom co‐doping led to an increased electrical conductivity of the material, in addition to appropriate particle size (10–20 μm in the sphere diameter) and specific surface area (7.7–14.4 m 2 g −1 ), the harmonious coexistence of graphite microcrystals and disordered regions, a larger average layer spacing between graphite phases, and the moderate presence of mesopores and macropores.…”
Section: Application Of Lignin Carbons In Electrochemical Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, heteroatom doping and loading of sodium storage particles on lignin‐derived hard carbon could also effectively improve the sodium storage performance. Zhang et al [ 112 ] used lignin as a carbon source to synthesize N, P co‐doped hard carbon microspheres with controlled microstructure and morphology by an emulsion‐solvent evaporation method mediated by (NH 4 ) 2 HPO 4 (Figure 13a). The results showed that N, P‐heteroatom co‐doping led to an increased electrical conductivity of the material, in addition to appropriate particle size (10–20 μm in the sphere diameter) and specific surface area (7.7–14.4 m 2 g −1 ), the harmonious coexistence of graphite microcrystals and disordered regions, a larger average layer spacing between graphite phases, and the moderate presence of mesopores and macropores.…”
Section: Application Of Lignin Carbons In Electrochemical Energy Storagementioning
confidence: 99%
“…Reproduced with permission: Copyright 2021, John Wiley and Sons. [112] | 293 T A B L E 4 Comparison of the sodium storage properties of different lignin-derived carbon materials Materials Reversible capacity Rate capability References C-1300 297 mAh g −1 (50 cycles, 50 mA g −1 ) 116 mAh g −1 (2.5 A g −1 ) [ 108] NLC 374 mAh g −1 (500 cycles, 25 mA g −1 ) 223 mAh g −1 (0.1 A g −1 ) [ 109]PL-1300 270 mAh g −1 (100 cycles, 50 mA g −1 ) 102 mAh g −1 (0.5 A g −1 )[ 111] 0.20NPL-1300 248 mAh g −1 (200 cycles, 100 mA g −1 ) 111 mAh g −1 (1 A g −1 )[ 112] HCM55-1400 316 mAh g −1 (150 cycles, 30 mA g −1 ) 161 mAh g −1 (0.3 A g −1 )[ 114] CLRSs 210 mAh g −1 (300 cycles, 125 mA g −1 ) 60 mAh g −1 (2.5 A g −1 )[ 115] CNF 122 mAh g −1 (350 cycles, 50 mA g −1 ) 25 mAh g −1 (1 A g −1 )[ 116] PL-CNFs 247 mAh g −1 (200 cycles, 100 mA g −1 ) 80 mAh g −1 (1 A g −1 )[ 117] E-KL/CA-C 340 mAh g −1 (200 cycles, 50 mA g −1 ) 103 mAh g −1 (0.4 A g −1 )[ 118] LC 202 mAh g −1 (100 cycles, 15 mA g −1 ) 45 mAh g −1 (0.15 A g −1 )[ 119]…”
mentioning
confidence: 99%
“…58 Phosphorus can enhance the charge leaving domains of carbon atoms and form active sites of carbon materials at edge positions. Zhang et al 59 could easily convert lignin into nanoporous N and P co-doped hard carbon microspheres using an emulsion-solvent evaporation process, and electrochemical measurements of sodium-ion batteries showed that such ligninderived carbon microspheres also follow the widely accepted adsorption-intercalation sodium storage mechanism. They exhibit quite excellent sodium storage performance, such as large reversible and low voltage capacity, high initial coulombic efficiency (78.7-82.4%), good rate capability, and long cycle stability.…”
Section: Remaining Hetero-atom Dopingmentioning
confidence: 99%
“…[2,3] However, the limited specific capacity and unsatisfactory Coulombic efficiency seriously limit the commercial application of hard carbon anode materials in sodium-ion batteries. [4,5] Recently, numerous solutions have been attempted to improve the electrochemical performance of hard carbon, including expanding interlayer d-spacing to accelerate intercalation and diffusion of Na + in graphitic-like domains; [6] providing more active adsorption sites on the surface by doping heteroatoms (e.g., N, [7] S, [8] F, [9] P, [10] etc.) and grafting functional groups; [11] optimizing the porous structure to form Na x+ (0≤x≤1) cluster storage within suitable pores; [12][13][14] and improving the initial Coulombic efficiency (ICE) by controlling the specific surface area and shielding defects.…”
Section: Introductionmentioning
confidence: 99%